Key Determinants of Health-Related Quality of Life Among Advanced Lung Cancer Patients: A Qualitative Study in Belgium and Italy - Janssens, Rosanne; Arnou, Reinhard; Schoefs, Elise; Petrocchi, Serena; Cincidda, Clizia; Ongaro, Giulia; Oliveri, Serena; Smith, Meredith Y.; Louis, Evelyne; Vandevelde, Marie; Nackaerts, Kristiaan; Pravettoni, Gabriella; et al. (Frontiers in Pharmacology, 2021)
Background: The lung cancer (LC) treatment landscape has drastically expanded with the arrival of immunotherapy and targeted therapy. This new variety of treatment options, each with its own characteristics, raises uncertainty regarding the key aspects affecting patients’ health-related quality of life (HRQL). The present qualitative study aimed to investigate how LC patients perceive their HRQL and the factors that they consider to be most influential in determining their HRQL. Methods: This qualitative research incorporates four focus group discussions, with six LC patients in each group. In total, 24 stage III and IV LC patients were included in the discussions, with Italian (n = 12) and Belgian (n = 12) patients, age range: 42–78, median age = 62 (IQR = 9.3 years), SD = 8.5; 62% men. Using thematic analysis, transcripts and notes from the FGDs were analyzed using NVivo software (edition 12). Results: Three main themes capturing determinants of HRQL were identified. First, patients agreed on the importance of physical aspects (symptoms and side-effects) in determining their HRQL. In particular, skin conditions, nausea, fatigue, risk of infections, sensory abnormalities, pain, and changes in physical appearance were highlighted. Second, patients worried about psychological aspects, negatively impacting their wellbeing such as uncertainties regarding their future health state, and a lower degree of autonomy and independence. Third, patients underlined the importance of social aspects, such as communication with healthcare providers and social interaction with friends, family and peers. Conclusion: This study demonstrates that physical, psychological, and social aspects are key factors driving LC patients’ HRQL. Gaining a better understanding of how LC patients perceive their HRQL and how it is affected by their illness and therapy will aid patient-centric decision-making across the drug life cycle, by providing stakeholders (drug developers, regulators, reimbursement bodies, and clinicians) insights about the treatment and disease aspects of importance to LC patients as well as the unmet needs LC patients may have regarding available treatment modalities. Finally, this study underscores a need for individual treatment decision-making that is considerate of uncertainties among LC patients about their future health state, and ways for improving communication between healthcare providers and patients to do so.